1976
DOI: 10.1021/ja00426a072
|View full text |Cite
|
Sign up to set email alerts
|

Thallium in organic synthesis. 43. Novel oxidative rearrangements with thallium(III) nitrate (TTN) in trimethyl orthoformate (TMOF)

Abstract: From the foregoing, it is apparent that treatment of a complex, substituted hydrocarbon substrate with either elemental fluorine or a fluoroxy reagent (with radical inhibitor) comprises an effective, predictable, and regioselective process for substitution a t saturated carbon.12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…102 "C/4 Torr; 79% isolated yield; 6, 1.70 (d, 3 H), 5.30 (q, 1 H), and 7. 4 Rearrangement Procedure.-A typical experimental procedure is as follows (reaction conditions and product yields are shown in Table 1). A mixture of 2-bromo-4'-isobutylpropiophenone (1; R = Bu', X = Br) (13.0 g, 50 mmol), TTN (22.2 g, 50 mmol), 70% perchloric acid (9.3 ml, 100 mmol), and TMOF (550 ml) was stirred at 25 "C for 25 h. About three-quarters of the TMOF was then distilled off under reduced pressure and the residue was treated with CHCI, (200 ml).…”
Section: Resultsmentioning
confidence: 99%
“…102 "C/4 Torr; 79% isolated yield; 6, 1.70 (d, 3 H), 5.30 (q, 1 H), and 7. 4 Rearrangement Procedure.-A typical experimental procedure is as follows (reaction conditions and product yields are shown in Table 1). A mixture of 2-bromo-4'-isobutylpropiophenone (1; R = Bu', X = Br) (13.0 g, 50 mmol), TTN (22.2 g, 50 mmol), 70% perchloric acid (9.3 ml, 100 mmol), and TMOF (550 ml) was stirred at 25 "C for 25 h. About three-quarters of the TMOF was then distilled off under reduced pressure and the residue was treated with CHCI, (200 ml).…”
Section: Resultsmentioning
confidence: 99%
“…The keto acetal (508) 423 was obtained through normal Ar ring migration, while the ester (512) was obviously achieved by migration of the Ar 1 ring. As shown in Scheme 150, owing to the low rate of the treatment of chalcone with TTN and also the faster reaction of aldehydes and ketones with TMOF by TTN to form acetals and ketals, 424 the ketalization reaction of chalcone apparently competes with oxidative rearrangement. Hence, the oxidative rearrangement resulted in product (508) 2-Dimethoxymethyl-4,4-dimethoxycyclohexa-2,5-dienone (514) could be prepared via oxidation of 2-formyl-4methoxyphenol (513) with TMOF (4), utilizing thallium trinitrate 426,427 in methanol at À20 C while the oxidation of 2methoxycarbonyl-4-methoxyphenol furnished 2methoxycarbonyl-3,4,4-trimethoxycyclohexa-2,5-dienone (Scheme 151).…”
Section: Acetalization Reactionmentioning
confidence: 99%
“…Many synthetic preparations reported for such acids, involve a useful oxidative rearrangement of alkyl aryl ketones by thallium(lll) nitrate trihydrate (TTN). [3][4][5] Lead(1v) salts often show similar reactivities to thallium(lI1) and mercury(l1) salts in the oxidation of organic compounds.6-8 Indeed, Myrboh et aL9 have reported that treatment of acetophenones with lead(1v) acetate and boron trifluoridediethyl ether in benzene-methanol give methyl arylacetates in high yield via the oxidative rearrangement of the aryl group. We now report the application of this rearrangement to propiophenones for the preparation of 2-arylpropanoic acids.…”
Section: Oxidative Rearrangement Of Aryl Ethyl Ketones T O Alkyl2-ary...mentioning
confidence: 99%
“…The amount of lead(1v) salt in the mixture was determined by iodimetry at appropriate time intervals. Alkaline Hydrolj,sis qf AIkj*l 2-A rylpropanoates (3).-The alkaline hydrolysis of (2) to free acids (3) was carried out following the procedure described in reference 10 (Table 5). The yield and purity of the acid were determined by g.1.c.…”
Section: )mentioning
confidence: 99%